Market integration and price transmission in Tajikistan’s wheat markets: Rising like rockets but falling like feathers? - Ilyasov, Jarilkasin; Götz, Linde; Akramov, Kamiljon T.; Dorosh, Paul A.; Glauben, Thomas (International Food Policy Research Institute, 2016)
The extent of market integration and transmission of food price shocks is a major determinant of price stability and overall food security, particularly in developing countries. Few studies have examined these issues for countries in Central Asia, however. This paper aims to fill this gap by examining wheat market integration and price transmission in Tajikistan, the most food-insecure country in Central Asia. In particular, in this study we measure how well wheat market prices in Tajikistan are integrated with international and regional markets, as well as domestically with each other. Subsequently, we assess the nature of price transmission between these markets. Using horizontal price transmission analysis and asymmetric price relationships, a.k.a. rockets and feathers, we demonstrate how prices change in peripheral food-shortage markets compared to markets located in zones with abundant local production.